A collaborative audit of the management of hypertension in general practice. Issue 869 (March 1998) - Raman, G. V.; Neal, A.; Lewis, C.
Abstract : We carried out an audit of the management of essential hypertension in general practice, against standards based on current guidelines. We examined the records of 882 hypertensive subjects (on medication) in whom hypertension had been diagnosed between January 1989 and December 1993, from 14 general practices in the Portsmouth and South East Hampshire Health Authority. The overall prevalence of hypertension was 3.5%. Pretreatment blood pressure had been measured on three or more occasions in 87% of patients. Pretreatment blood pressure was equal to or greater than 150/95 mmHg in 96% and 160/100 mmHg in 86.5% of patients. A thiazide diuretic was the initial drug of choice in 30% of patients, with beta-blockers being the most popular initial treatment. Ninety per cent of patients had had their blood pressure measured at least once during the preceding year. In 82.5% of patients, current blood pressure was less than 150/95 mmHg, while 44% achieved a current blood pressure less than 140/90 mmHg. We conclude that the prevalence of hypertension in this population was lower than expected, suggesting the need for improved screening. We also propose that the initial treatment choice should be a thiazide in the majority, which would result in significant cost saving. The blood pressure control was suboptimal compared to current guidelines.